Awesomely Emma : a Charley and Emma story - Webb, Amy, 1977-; Liddiard, Merrilee (Minneapolis : Beaming Books, 2020)
When she encounters problems that diminish her enjoyment of a class field trip to a local art museum, Emma calls on her inner sense of awesome to stand up for herself and teach her friend Charley how to feel comfortable in his own skin.
School Library Journal, July 2020
2.3
K-3
Some copies purchased with funds from CPSF Equity Grant - 2022
AD530L
Keywords: Individuality -- Juvenile fiction; Ability -- Juvenile fiction; People with disabilities -- Juvenile fiction; School field trips -- Juvenile fiction; Art museums -- Juvenile fiction; Individuality -- Fiction; Ability -- Fiction; People with disabilities -- Fiction; School field trips -- Fiction; Art museums -- Fiction